The Effect of Self Efficacy, Communication, and Financial Compensation on Employee Performance - Luluk Herwana; Prayekti Prayekti; Epsilandri Septyarini (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Self-efficacy is defined as a human belief in its ability to adapt to every condition and situation it faces. Communication is a person's way of expressing the desired opinion according to income, the point is that good communication can create job satisfaction. Financial Compensation is compensation for services provided by employees to organizations that can be in the form of money or goods to increase the morale of employee performance. Employee performance is the key to the success of an organization that can be achieved because of the results of employee performance. The purpose of this study was to examine the effect of self-efficacy, communication, and financial compensation on employee performance. The population in this study was 50 employees who worked in the Tourism Office of Gunungkidul Regency. By using a saturated sampling technique, the sample used is all employees (50 respondents). The sampling technique in this study used saturated sampling. The data analysis method used is Linear Regression. The results of this study indicate that: Self-efficacy and communication have a positive and significant effect on employee performance as evidenced by the output where tcount> ttable. While financial compensation is not significant to employee performance, this is evidenced by the output where the tcount value is greater than the ttable.